Photodynamic effect of glycochlorin conjugates in human cancer epithelial cells. Issue 42 (9th April 2015) - Gomes, A. T. P. C.; Faustino, M. A. F.; Neves, M. G. P. M. S.; Ferreira, V. F.; Juarranz, A.; Cavaleiro, J. A. S.; Sanz-Rodríguez, F.
Abstract : The effect of glycochlorins in HeLa cells shows that the galactose conjugate is the most efficient photosensitizer. Abstract : The photodynamic effect of glycochlorins 1–4 was evaluated for the first time in human epithelial cells (HeLa) and their PDT efficiency was compared with the results obtained when using human normal skin keratinocytes cells (HaCaT). It was demonstrated that the galactose conjugate is the only photosensitizer that is selective for HeLa cells, without causing a significant effect on the HaCaT cells. Morphological studies carried out after the photodynamic treatment attested such selectivity and showed that HeLa cells suffer a strong cytoplasmic vacuolization and a pronounced retraction, while in HaCaT cells the damage, under the same protocol conditions, is scarce.